To find the amount of change (c) Mela receives after purchasing the shoes for $40.99, you can set up the following equation:
\[ 50 - 40.99 = c \]
This can be rearranged into the form of an appropriate equation:
\[ c + 40.99 = 50 \]
This equation indicates that the amount of change (c) plus the cost of the shoes ($40.99) equals the amount given to the cashier ($50).
Now, to calculate the change:
\[ c = 50 - 40.99 \] \[ c = 9.01 \]
So, Mela receives $9.01 in change.
The correct statement from the provided responses is:
c + 40.99 = 50; Mela receives $9.01 in change.